The Role of the Sarak Opat in Resolving Minor Crimes - Suhartini, Suhartini; Surya, Achmad (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
The Sarak Opat as one of the customary institutions in Aceh have been authorized to settle disputes of minor cases at the village level in Central Aceh, Aceh, Indonesia. This is guaranteed by the applicable laws and regulations. However, the practice of resolving minor cases is currently delegated to the judiciary. Therefore, this study was a legal empirical or sociological research to analyze primary and secondary data in Central Aceh Regency. Data collection method employed were direct interviews with selected informants, and the collected data were processed in qualitative analysis method. The results showed that the role of the Sarak Opat customary institution in resolving minor cases in the Gayo community in Central Aceh has a strong legal basis as mandated by various national and regional legal policies. Subsequently, the customary institution has two considerations in delegating minor criminal cases to the judiciary. First, the litigants are dissatisfied with the sanctions decided by Sarak Opat. Second, the officials of Sarak Opat lack understanding of their authority as a customary justice institution.